Efeito da plataforma vibratória no perfil bioquímico, estresse oxidativo e morfologia dos tecidos hepático e adiposo de ratos Wistar obesos - Andrade, Bárbara Zanardini de (2019)
Obesity is an aggravating factor for associated diseases and an alarming public health problem. In order to control it, several treatments have been used which physical exercises represent a less invasive alternative. However, not all modalities are indicated, because of obesity comorbidities associated, in this sense, whole body vibration (WBV) is a physical exercise form that has been gaining prominence. The present study evaluated WBV treatment in metabolism lipid, oxidative stress and morphology of adipose and hepatic tissues of Wistar rats, obese by monosodium glutamate (MSG). Therefore, thirty-eight rats were divided in groups: Control Sedentary (CTL-SED) and MSG Sedentary (MSG-SED): treated from the 1st to 5th day of age with saline and MSG, respectively, and not WBV exercised; Control Vibration (CTL-VB) and MSG Vibration (MSG-VB): treated with saline or MSG and who underwent WBV exercise for eight weeks. Weekly weight gain and food intake were observed. Before the exercise begin, the Intraperitoneal Glucose Tolerance Test (ipGTT) and the insulin dosage were executed. Which were repeated at the end of the treatment and then, performed Lee Index calculation and euthanasia. Samples taken from fat and liver were used for histomorphometric analysis. Triglyceridemia and cholesterolemia were also evaluated, besides triglycerides, cholesterol, catalase, superoxide dismutase and lipoperoxidation quantified in the liver., Obese animals (MSG-SED and MSG-VB) had a reduction in glycemia in the pre-exercise period when compared to control animals (CTL-SED and CTL-VB), but similar between the groups in post-exercise period. In addition, the obese animals presented normofagia, greater fat accumulation, Lee index, triglyceridemia and cholesterolemia and lower weight gain. In the liver, there were higher concentrations of triglycerides, cholesterol and lipoperoxidation, besides catalase with reduced activity. In the histomorphometric analysis, there was an increase in retroperitoneal adipocytes area and onset liver lipid deposition. WBV exercise reduced the Lee index in control animals (CTL-VB), but exacerbated triglyceridemia, cholesterolemia and hepatic lipoperoxidation in obese animals (MSG-VB). On the other hand, there was heterogeneity in adipocytes area in the CTL-VB and MSG-VB groups. Thus, the WBV had specific effects on the model, indicating that protocol modifications could have an effect on others parameters evaluated.